1995
DOI: 10.1111/j.1476-5381.1995.tb16423.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by cyclo‐oxygenase inhibitors of platelet‐activating factor production in thapsigargin‐stimulated macrophages

Abstract: 1 Thapsigargin stimulated the accumulation of cell-associated platelet-activating factor (PAF) and extracellular prostaglandin E (PGE2) in rat peritoneal macrophages. PAF in the conditioned medium was less than the detectable amount. To obtain further insight into the mechanism of PAF accumulation, the role of PGE2 in PAF accumulation was investigated. 2 When macrophages were incubated in medium containing thapsigargin (30 ng ml-', 46.1 nM) and cyclo-oxygenase inhibitors such as indomethacin, naproxen or ibupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Thapsigargin and TPA at very low concentrations induce arachidonic acid release, the production of prostaglandin (PG) E 2 , platelet‐activating factor (PAF) and various cytokines in rat peritoneal macrophages (Ohuchi et al ., 1988; Watanabe et al ., 1995; Yamada et al ., 1998). In the present study, we found that thapsigargin and TPA also increase histamine contents in the conditioned medium of RAW 264.7 cells (Figures 1a,b and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Thapsigargin and TPA at very low concentrations induce arachidonic acid release, the production of prostaglandin (PG) E 2 , platelet‐activating factor (PAF) and various cytokines in rat peritoneal macrophages (Ohuchi et al ., 1988; Watanabe et al ., 1995; Yamada et al ., 1998). In the present study, we found that thapsigargin and TPA also increase histamine contents in the conditioned medium of RAW 264.7 cells (Figures 1a,b and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of prostaglandin whose synthesis is mediated by cyclooxygenase (COX), a prostaglandin endoperoxide synthase, play a significant role in inflammatory reactions (Davies et al 1984). COX has two isoforms : COX-1 is constitutively expressed in almost all types of cells (O'Neill & Ford-Hutchinson 1993 ;Smith et al 1994) and is probably involved in cellular housekeeping (DeWitt & Smith 1988) ; COX-2 is induced by several kinds of extracellular stimuli (Ali et al 1985 ;Ohuchi et al 1988 ;Nishizuka 1992 ;O'Sullivan et al 1992 ;Dubois et al 1994 ;Watanabe et al 1995) in inflammatory cells and tissues (Lee et al 1992 ;Sano et al 1992 ;Yamada et al 1997 ;Yamashita et al 1997). This suggests that the stimulation of arachidonic acid metabolism at the inflammatory site is due to the induction of COX-2 protein in the inflammatory cells by such stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and pharmacological analyses have shown that the major bioactive compounds synthesized by the plant are the two polyoxygenated guaianolides named thapsigargin and thapsigargicin. In particular, they have been recognized as powerful non-cytotoxic histamine liberators, stimulants of different cells of the immune system (CHRISTENSEN et al 1992), non-TPA tumor promoters (HAKII et al 1986;WATANABE et al 1995) and selective inhibitors of SERCA-ATP-ases in animal cells (JANCZEWSKI and LAKATTA 1993; INESI and SAGARA 1994; CHRTS-TENSEN et a]. 1997).…”
mentioning
confidence: 99%